O040 Patient reported outcomes and experiences following emergency laparotomy: a mixed methods patient survey. (22nd July 2022) - Silva, L; Mohammed, SA; Strong, P; Watts, T; Torkington, J; Cornish, J
Abstract: Introduction: Emergency laparotomy (EmLap) is a "life-saving" procedure, but little is known about how "life-changing" it can be. This study aims to establish the impact of EmLap on PROMs and PREMs. Methods: All surviving patients who had an EmLap from 2016–2019 were included. Eligible patients were invited to complete a postal questionnaire. Responses underwent qualitative and logistical regression analysis. Results: Response rate was 42.6% (n=310). 11.3% reported that they had not resumed intimacy post-op. Patients were less likely to resume intimacy if they were >80 years (OR 10.500, p 0.003), had a return to theatre (OR 5.111, p 0.017), IBD diagnosis (OR 5.00, p 0.009) or stoma (OR 4.906, p 0.003). Patients were more likely to change employment if female (OR 2.858, p 0.009), more comorbid (ASA3 OR 5.000, p 0.024), had a stoma (OR 4.006, p <0.001), or incisional hernia (OR 4.228, p <0.001). Qualitative analysis revealed deconditioning, lack of employer support, and delays to reconstructive surgery were the main reasons for not returning to work. Qualitative analysis of experience exposed a number of unmet needs: surgical "debrief" and "what to expect" (33.6%), surgical aftercare (25.2%), mental-health support (22.6%) and timely restorative surgery (11.7%). 88.1% felt a specialist nurse would have improved their experience. Patients were more likely to have reported a negative experience if they had benign disease (p0.010). Conclusion: This is the first study to describe PROMS and PREMS following EmLap, and also to identify patients at risk of poor outcome. It advocates the need for an EmLap specialist nurse to facilitate holistic care.